Pengaruh Bentuk Debu Terhadap Minimum Ignition Energy (MIE) Pada Debu Serbuk Kayu - Udyani, Kartika (Institut Teknologi Adhi Tama Surabaya, 2025)
Dust explosion is a serious threat in industries that involve the processing and storage of powdery materials, such as flour, sugar, wood, and so on. The aim of this study was to determine the effect of dust shape on MIE. Irregular and spherical wood dust was dried for 1 hour, 2 hours, 3 hours, 4 hours and 5 hours and then tested for moisture content. Samples dried for 1 hour had a moisture content of about 13%. Samples dried for 2 hours have a moisture content of about 9%. The sample dried for 3 hours has a moisture content of about 7%. The sample dried for 4 hours has a moisture content of about 6.5%. Samples dried for 5 hours have a moisture content of about 6%. After knowing the water content, each sample is weighed as much as 1 gram; 1.25 grams; 1.5 grams; 1.75 grams; 2 grams and then tested using a Dust Explosion tool. Irregular samples have the highest MIE value of 6.3801 mJ and the smallest of 1.3936 mJ. Spherical samples have the highest MIE value of 7.7079 mJ and the smallest of 1.3951 mJ. The highest MIE value is at a concentration of 1 g/L and the smallest at a concentration of 2 g/L.